Implementasi Load Balancing Web Server dengan Algoritma Source IP Hash pada Software Defined Network (SDN) - Anita Sumiati; Primantara Hari Trisnawan; Mochammad Ali Fauzi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Software Defined Networking (SDN) is a network architecture that separates the control plane from the data plane. SDN network architecture divides incoming requests to be given to a server. SDN uses OpenFlow version 1.3 as a protocol and load balancing to distribute the load on two or even more balanced network connections. Load balancing has an algorithm that is use to distribute requests to each server. There were several algorithms that have been used before, one of them is the least traffic algorithm. This research uses the Source IP Hash algorithm, and Ryu as the controller that functions to allocate the server by doing a hash on the source IP address. This algorithm is tested and analyzed its performance on, response time, throughput, and packet loss. The throughput value of the source IP hash algorithm reaches 206 mbps while the least traffic algorithm is 106 mbps. Packet Loss that occured in the source IP hash algorithm is 0% while the least traffic algorithm experienced packet loss with the category high as much as 4.009%. From the two results of throughput and packet loss tested, it is concluded that the source IP hash algorithm handles requests from clients better than least traffic. The Source IP Hash algorithm could allocated the same source IP address to the same server, while the least traffic algorithm must selected the server by making a loop based on low traffic.